Changes in Healthcare Utilization, Spending, and Perceived Health during COVID–19: A Longitudinal Study from Singapore - SangNam Ahn; Seonghoon Kim; Kanghyock Koh (Institute of Labor Economics (IZA), 2020)
The COVID–19 pandemic has challenged the capacity of healthcare systems around the world and can potentially compromise healthcare utilization and health outcomes among non-COVID–19 patients. Using monthly panel data of nationally representative middle-aged and older Singaporeans, we examined the associations of the pandemic with healthcare utilization, out-of-pocket medical costs, and perceived health. At its peak, doctor visits decreased by 30% and out-of-pocket medical spending decreased by 23%, mostly driven by reductions in inpatient and outpatient care. Although there were little changes in self-reported health and sleep quality, COVID–19 increased depressive symptoms by 4%. We argue that it is imperative to monitor COVID–19's long-term health effects among non-COVID–19 patients since our findings indicated delayed healthcare and worsened mental health during the outbreak.
Keywords: I12; I18; 330; COVID–19; pandemic; healthcare utilization; healthcare spending; self-reported health status; mental health